Implementasi Sanitasi Data Pada Sistem Operasi Android dengan Metode Gutmann - Trisnawan, Muhammad Yus Aditya; Beeh, Yos Richard (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Data security and privacy are essential for all mobile device users, especially Android. However, deleted data can generally still be recovered using forensic analysis of the storage media hardware with data recovery software. For this reason, you need a data deletion application capable of deleting safely. Many methods are available for safe deletion, such as applying different numbers of passes (overwriting). This research proves that most available methods cannot be deleted entirely and can be recovered, so a data deletion application was created using the most up-to-date method, the Gutmann Method. This method uses 35 number of operands to overwrite the file. Applications are made by analyzing system requirements and implementing them into mobile programming. Then, a comparison test is carried out with other existing applications. The results show that applications created using the Gutmann method are 33% less likely to find file traces than the best comparison application.